An Initial Evaluation on the Adsorption of SO2 and NO2 over Porous Fe3O4 Nanoparticles Synthesized by Facile Scalable Method - Xuan-Manh Pham; Duy Linh Pham; Nguyen Thi Hanh; Tuyet Anh Dang Thi; Le Nhat Thuy Giang; Hoang Thi Phuong; Nguyen Tuan Anh; Hac Thi Nhung; Giang Truong Le; Mai Ha Hoang; Tuyen Van Nguyen (Journal of Chemistry)
In this study, Fe3O4 nanoparticles used as an adsorbent for the removal of toxic gases were successfully synthesized via the facile coprecipitation method. The Fe3O4 nanoparticles displayed a well-defined morphology with the size of ∼10 nm and a porous structure with a specific area of 115.90 m2/g and a wide range of pore sizes. These nanoparticles exhibited effective adsorption abilities upon the exposure to toxic gases. In particular, the amount of 40.5 mg SO2 and 108.5 mg NO2 was adsorbed in 1 g of Fe3O4 nanoparticles after 60 minutes of exposure, making the Fe3O4 nanoparticles become a promising adsorbent for the removal of toxic gases.